Actions speak louder than words: Differences in memory flexibility between monolingual and bilingual 18‐month‐olds. Issue 2 (4th July 2019) - Barr, Rachel; Rusnak, Sylvia N.; Brito, Natalie H.; Nugent, Courtney
Abstract: Bilingual infants from 6‐ to 24‐months of age are more likely to generalize, flexibly reproducing actions on novel objects significantly more often than age‐matched monolingual infants are. In the current study, we examine whether the addition of novel verbal labels enhances memory generalization in a perceptually complex imitation task. We hypothesized that labels would provide an additional retrieval cue and aid memory generalization for bilingual infants. Specifically, we hypothesized that bilinguals might be more likely than monolinguals to map multiple perceptual features onto a novel label and therefore show enhanced generalization. Eighty‐seven 18‐month‐old monolingual and bilingual infants were randomly assigned to one of two experimental conditions or a baseline control condition. In the experimental conditions, either no label or a novel label was added during demonstration and again at the beginning of the test session. After a 24‐hr delay, infants were tested with the same stimulus set to test cued recall and with a perceptually different but functionally equivalent stimulus set to test memory generalization. Bilinguals performed significantly above baseline on both cued recall and memory generalization in both experimental conditions, whereas monolinguals performed significantly above baseline only on cued recall in both experimental conditions. These findings show a difference between monolinguals and bilinguals in memory generalization and suggest that generalization differences between groups may arise from visual perceptual processing rather than linguistic processing. A video abstract of this article can be viewed at https://youtu.be/yXB4pM3fF2k Abstract : Both monolingual and bilingual infants showed evidence of cued recall but only bilingual 18‐month‐olds generalized across stimuli after a 24‐hour delay. Generalization patterns did not differ as a function of a label. These findings show a difference between monolinguals and bilinguals in memory generalization and suggest that generalization differences between groups may arise from visual perceptual processing rather than linguistic processing.